Advanced Imaging of Intracranial Atherosclerosis: Lessons from Interventional Cardiology - Pavlin-Premrl, Davor; Sharma, Rahul; Campbell, Bruce C. V.; Mocco, J.; Opie, Nicholas L.; Oxley, Thomas J. (Frontiers in Neurology, 2017)
Intracranial atherosclerosis is a major cause of ischemic stroke. Patients with a high degree of stenosis have a significant rate of stroke despite medical therapy. Two randomized trials of stenting have failed to show benefit. Improving peri-procedural complication rates and patient selection may improve stenting outcomes. Fractional flow reserve (FFR), intravascular ultrasound (IVUS) and optical coherence tomography (OCT) are intravascular imaging techniques employed to improve patient selection and stent placement in interventional cardiology. FFR has been shown to improve cardiovascular outcomes when used in patient selection for intervention. Studies of FFR in intracranial atherosclerosis show that the measure may predict which plaques lead to stroke. IVUS is used in cardiology to quantify stenosis and assist with stent placement. Comparisons with histology show that it can reliably characterize plaques. Several case reports of IVUS in intracranial arteries show the technique to be feasible and indicate it may improve stent placement. Plaque characteristics on IVUS may help identify vulnerable plaques. In interventional cardiology, OCT provides excellent visualization of vessel geometry and is useful peri-procedurally. Images reliably identify thin-capped fibroatheromas and other plaque features. Case reports indicate that OCT is safe for use in intracranial arteries. OCT can be used to identify perforator vessels and so may be useful in avoiding perforator strokes, a common complication of stenting. Plaque characteristics on OCT may be useful in patient selection.